ETHICS IN MODERN SOCIETY: CHALLENGES AND RESPONSIBILITIES - Yo‘ldoshxo‘jayeva Dilshodaxon (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This article explores the evolving role of ethics in modern society amid the challenges posed by technological advancements, globalization, and digital communication. It defines ethics as a system of moral principles that not only guide individual actions but also shape societal institutions and norms. The article highlights the complexity of ethical considerations in today’s world, particularly with the blurring lines between the public and private spheres, exacerbated by the rise of digital spaces. A key point discussed is the emergence of digital ethics, a field concerned with responsible behavior in digital environments where accountability remains ambiguous. The article also addresses the ethical relativism that arises due to globalization, emphasizing the difficulty of establishing universal ethical standards while respecting cultural differences. By analyzing these evolving ethical challenges, the article underscores the importance of ethical education and responsibility in guiding society through contemporary moral dilemmas.